The Complementarity Effect of Intensive and Extensive Margins of Exports Diversification on Growth: Empirical Evidence from Nigerian Data - Young Ademola; Ogbaro Eyitayo; Ologundudu Mojeed (Folia Oeconomica Stetinensia)
Two main theoretical patterns of exports diversification have evolved in development economics: the intensive- and extensive-export margins. Myriads of studies have assessed the relative merits of both patterns of diversification in promoting economic growth. Empirical literature, however, has thus far produced mixed and inconclusive results.